Comparative Genomic and Transcriptomic Analyses of Mycobacterium kansasii Subtypes Provide New Insights Into Their Pathogenicity and Taxonomy - Guan, Qingtian; Ummels, Roy; Ben-Rached, Fathia; Alzahid, Yara; Amini, Mohammad S.; Adroub, Sabir A.; van Ingen, Jakko; Bitter, Wilbert; Abdallah, Abdallah M.; Pain, Arnab (Frontiers in Cellular and Infection Microbiology, 2020)
Mycobacterium kansasii is an important opportunistic pathogen of humans and has a close phylogenetic relationship with Mycobacterium tuberculosis. Seven subtypes (I-VII) have been identified using molecular biology approaches, of which subtype I is the most frequent causative agent of human disease. To investigate the genotypes and pathogenic components of M. kansasii, we sequenced and compared the complete base-perfect genomes of different M. kansasii subtypes. Our findings support the proposition that M. kansasii “subtypes” I-VI, whose assemblies are currently available, should be considered as different species. Furthermore, we identified the exclusive presence of the espACD operon in M. kansasii subtype I, and we confirmed its role in the pathogenicity of M. kansasii in a cell infection model. The espACD operon is exclusively present in mycobacterial species that induce phagosomal rupture in host phagocytes and is known to be a major determinant of ESX1-mediated virulence in pathogenic mycobacteria. Comparative transcriptome analysis of the M. kansasii I-V strains identified genes potentially associated with virulence. Using a comparative genomics approach, we designed primers for PCR genotyping of M. kansasii subtypes I-V and tested their efficacy using clinically relevant strains of M. kansasii.